Pengaruh Pendidikan Kewirausahaan dan Motivasi terhadap Minat Berwirausaha: Study Kasus Mahasiswa STIE Binakarya Tebing Tinggi - Ermayori Lumban Raja; Rifka Tamara Hutabarat; Rusmewahni Rusmewahni; Imelda Mardayanti (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2026)
This study aims to analyze the influence of entrepreneurship education and motivation on students' entrepreneurial interest. The background of this study is based on the low interest of students in entrepreneurship despite having received entrepreneurship education at university. This study uses a quantitative approach with an associative method. The study population was students of the Management Study Program, Class of 2022, STIE Bina Karya Tebing Tinggi, with a purposive sampling technique in accordance with certain criteria determined by the researcher. Data were collected through questionnaires and analyzed using multiple linear regression. The results show that motivation has a positive and significant effect on entrepreneurial interest, while entrepreneurship education has no significant effect partially. However, simultaneously, both variables have a significant effect on entrepreneurial interest. The coefficient of determination shows that the variables of entrepreneurship education and motivation can explain 54.8% of entrepreneurial interest, while the remainder is influenced by other factors outside the study. The implications of this study emphasize the importance of increasing motivation and strengthening more practical entrepreneurship learning to be able to encourage student interest in entrepreneurship.